Focusing Telescopes in Nuclear Astrophysics 2006
DOI: 10.1007/978-1-4020-5304-7_37
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo study of detector concepts for the MAX Laue lens gamma-ray telescope

Abstract: Abstract. MAX is a proposed Laue lens gamma-ray telescope taking advantage of Bragg diffraction in crystals to concentrate incident photons onto a distant detector. The Laue lens and the detector are carried by two separate satellites flying in formation. Significant effort is being devoted to studying different types of crystals that may be suitable for focusing gamma rays in two 100 keV wide energy bands centered on two lines which constitute the prime astrophysical interest of the MAX mission: the 511 keV p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…In particular, the 10 43 e + /s concentrated in the galactic center region, as well as the highly spherical morphology are a challenge to achieve from most galactic sources, which tend to trace the disk. Alternative explanations, such as low mass X-ray binaries (LMXBs) [11] could possibly provide a candidate [12], although no point source 511 keV emission has yet been observed [13]. Likewise, it has been suggested that the transport of the positrons produced in the galactic disk into the galactic center could provide the rate [14], although the precise dynamics that achieves this and yields such a spherical morphology is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the 10 43 e + /s concentrated in the galactic center region, as well as the highly spherical morphology are a challenge to achieve from most galactic sources, which tend to trace the disk. Alternative explanations, such as low mass X-ray binaries (LMXBs) [11] could possibly provide a candidate [12], although no point source 511 keV emission has yet been observed [13]. Likewise, it has been suggested that the transport of the positrons produced in the galactic disk into the galactic center could provide the rate [14], although the precise dynamics that achieves this and yields such a spherical morphology is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the fine voxelization would enable the selection of events from the core of the focal spot on the detector, which are more likely non-background events. In [4] and [5] it has been shown that voxel based (Compton) detectors outperform simple monolithic detectors. Therefore only those are considered in the following analysis.…”
Section: A Design Optionsmentioning
confidence: 97%
“…The focal planes vary widely in size and complexity as well as in shielding approach. Each focal plane is placed on top of a generic spacecraft model [4].…”
Section: B Simulation Modelsmentioning
confidence: 99%
“…We shall precise that the performance of Laue lens telescopes could even be enhanced if a Compton telescope is put at the focus. 15 It this case it has been shown that the background rejection is improved leading to a sensitivity increased by a factor of two. On the other hand, if the first layers of the focal plane Compton camera are made of Silicon, it allows polarization measurement down to ∼ 100 keV.…”
Section: Performance Estimatesmentioning
confidence: 99%